Privacy, Education and Human Dignity - Hilcenko, Christine; Taubman-Bassirian, Tara (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
Access to knowledge for everyone in the increasingly-interconnected society has been a tool for democracy. We discuss here the dangers of a world online and the growing concerns about state surveillance, security, privacy and exploitation. We discuss our right to protect our individual freedom. We conclude that privacy is a fundamental Human Rights in order to guarantee human dignity and freedom.